2003
DOI: 10.1002/ejic.200390193
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Energy Transfer in Supramolecular, Hydrogen‐Bonded Polypyridylruthenium‐Osmium Complexes

Abstract: Hydrogen bond association between ruthenium bibenzimidazole and carboxylated polypyridylosmium complexes results in stable supramolecular aggregates. The determined stability constant of logK ഠ 6 ± 0.3 allows efficient energy transfer from the ruthenium to the osmium moiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…Earlier Beauchamp and co‐workers had shown that rhenium(III) complexes with biimidazole ligands not only bind halide anions via hydrogen bonds but also form hydrogen bond networks with benzoate anions . Energy transfer processes between metal complexes as well as organic triplet emitters and metal complexes have also been observed for hydrogen bonded systems which consisted of the biimidazole‐carboxylate motive . We were able to show that DNB quenches the phosphorescence of 12 by about 50 % in a 1:1 mixture in chloroform, and further addition of up to 8 equivalents leads to a residual luminescence of only about 8 % with respect to the pristine complex.…”
Section: Sensors For Small Anionssupporting
confidence: 52%
“…Earlier Beauchamp and co‐workers had shown that rhenium(III) complexes with biimidazole ligands not only bind halide anions via hydrogen bonds but also form hydrogen bond networks with benzoate anions . Energy transfer processes between metal complexes as well as organic triplet emitters and metal complexes have also been observed for hydrogen bonded systems which consisted of the biimidazole‐carboxylate motive . We were able to show that DNB quenches the phosphorescence of 12 by about 50 % in a 1:1 mixture in chloroform, and further addition of up to 8 equivalents leads to a residual luminescence of only about 8 % with respect to the pristine complex.…”
Section: Sensors For Small Anionssupporting
confidence: 52%
“…The discontinuities at 1 equiv. preclude determination of the association constant ( K a ) for the biimidazole–carboxylate interaction, but prior studies have revealed K a values of the order of 10 5 –10 6 M –1 for this type of salt bridge 9a,10. The fact that there is a discontinuity for all four signals in Figure 2 strongly suggests that the type of cation–anion interaction changes fundamentally when more than 1 equiv.…”
Section: Resultsmentioning
confidence: 98%
“…This includes, for example, hydrogen‐bonded cation–anion adducts between amidinium cations and carboxylates that mimic the naturally occurring salt bridges mentioned above 6. Cationic metal complexes of 2,2′‐biimidazole (biimH 2 ) and 2,2′‐bibenzimidazole (bibzimH 2 ) have been reported to form hydrogen‐bonded pairs with carboxylates7 as well as other anions,8 and this has opened the possibility for investigations of photoinduced charge9 and energy transfer10 within such adducts.…”
Section: Introductionmentioning
confidence: 99%
“…24). 52 Although, the system studied is very sensitive to hydrogen bond disruptors (e.g. water), in dry aprotic solvents efficient energy transfer could be observed using a combination of luminescence and single photon counting techniques.…”
Section: 47mentioning
confidence: 99%